The stress shadow problem in physics‐based aftershock forecasting: Does incorporation of secondary stress changes help?. Issue 11 (6th June 2014) - Segou, M.; Parsons, T.
Abstract Main shocks are calculated to cast stress shadows across broad areas where aftershocks occur. Thus, a key problem with stress‐based operational forecasts is that they can badly underestimate aftershock occurrence in the shadows. We examine the performance of two physics‐based earthquake forecast models (Coulomb rate/state (CRS)) based on Coulomb stress changes and a rate‐and‐state friction law for their predictive power on the 1989 Mw = 6.9 Loma Prieta aftershock sequence. The CRS‐1 model considers the stress perturbations associated with the main shock rupture only, whereas CRS‐2 uses an updated stress field with stresses imparted by M ≥ 3.5 aftershocks. Including secondary triggering effects slightly improves predictability, but physics‐based models still underestimate aftershock rates in locations of initial negative stress changes. Furthermore, CRS‐2 does not explain aftershock occurrence where secondary stress changes enhance the initial stress shadow. Predicting earthquake occurrence in calculated stress shadow zones remains a challenge for stress‐based forecasts, and additional triggering mechanisms must be invoked.